Metastable equilibrium of substitution reactions among oxygen- and nitrogen-bearing organic compounds at hydrothermal conditions. (1st March 2020) - Robinson, Kirtland J.; Fecteau, Kristopher M.; Gould, Ian R.; Hartnett, Hilairy E.; Williams, Lynda B.; Shock, Everett L.
Abstract: Measured abundances of organic compounds can reveal information about the environments in which they formed. Since organic compounds can be mobilized and released from geologic and planetary settings, they have the potential to provide insights into environments that are difficult to observe directly. To advance our understanding of these environments, this study identifies organic reactions that approach metastable equilibrium in experiments, so that future studies can predict geochemical conditions in remote settings (e.g., deep Earth, extraterrestrial bodies) by monitoring reaction ratios of compounds involved in similar organic reactions. At high temperatures organic redox reactions can equilibrate, which allows comparisons with thermodynamic properties to yield estimates of reaction conditions. However, redox reactions may equilibrate too slowly to be applicable to lower temperature systems. To explore metastable equilibria at lower temperatures, we studied substitution reactions that tend to be faster than redox reactions. In this study, we demonstrate that oxygen- and nitrogen-bearing organic compounds at hydrothermal conditions undergo a series of simultaneous substitution reactions that rapidly approach steady-state ratios indicative of metastable equilibrium. Four sets of aqueous experiments were performed at 250 °C and 40 bar, each beginning with a single organic reactant: benzyl alcohol, benzylamine, dibenzylamine, or tribenzylamine. All reactant solutions were prepared with identical bulk elemental compositions by adjusting the concentrations of the starting organic compounds and adding ammonia as needed. After 2 h at hydrothermal reaction conditions, all of the model compounds were detectable in all four sets of experiments, evidence for reversibility of reactions among the compounds. After 72 h, reaction ratios between the model compounds converged in all four sets of experiments, consistent with approaches toward metastable equilibrium. Reaction ratios for ether and aldehyde formation reactions were also observed to group within a relatively small range, but without a clear convergence pattern, suggesting other non-redox reactions may approach metastable equilibrium. The approach to metastable equilibrium among the initial organic reactants could be observed and quantified even in the presence of competing redox reactions whose mechanisms are less understood, including dibenzylimine and toluene formation, which did not appear to reach steady-states. These findings identify classes of organic compounds and reactions that can reflect the conditions at which they last equilibrated and should be targeted for analysis in natural systems.